Are Customers Behaving Differently in the Post-COVID-19 Era, and How is this Affecting Worker Satisfaction? - Joudeh, Jamal M. M.; Allan, Mahmoud; Abu-Loghod, Nabil A.; Khader, Jameel A.; Al-Gasawneh, Jassim A. (International Journal of Membrane Science and Technology, 2023)
A coronavirus (COVID-19) outbreak began in December 2019 in Wuhan, China. Since then, it has rapidly spread over the world, resulting in one of the deadliest pandemics in recent history in terms of infections and deaths. As a result, the objective of the present study is to investigate how the behavior of customers affects the psychological, physical, financial, and satisfaction levels of workers in small businesses post-COVID-19. To fulfill the objective of this study, a self-administered questionnaire was developed to measure the study’s variables. The questionnaire has been distributed by hand and online to 465 workers in small businesses in Jordan. The PLS-SEM of AMOS is applied to examine the hypotheses. The findings show that the behavior of customers has a direct positive impact on the psychological, health, and financial risks of workers who work in small businesses. Also, the findings show that psychological, health, and financial risks have a direct positive effect on the satisfaction of workers. Furthermore, it was discovered that customer behavior has an indirect positive impact on worker satisfaction via psychological, health, and financial risks. This study suggests that workers and customers should take action to safeguard themselves against future health crises. Customers and workers are advised to use masks, sanitizer, and social distancing when necessary. Workers and customers need to remember that their behaviors protect them as well as those who come into contact with them.